External Measures of Cognition - Cairo, Osvaldo (Frontiers in Human Neuroscience, 2011)
The human brain is undoubtedly the most impressive, complex, and intricate organ that has evolved over time. It is also probably the least understood, and for that reason, the one that is currently attracting the most attention. In fact, the number of comparative analyses that focus on the evolution of brain size in Homo sapiens and other species has increased dramatically in recent years. In neuroscience, no other issue has generated so much interest and been the topic of so many heated debates as the difference in brain size between socially defined population groups, both its connotations and implications. For over a century, external measures of cognition have been related to intelligence. However, it is still unclear whether these measures actually correspond to cognitive abilities. In summary, this paper must be reviewed with this premise in mind.